Economic Democracy - George, Donald A. R. author. aut Link
XII, 226 p.
Keywords: Explains the causes and consequences of democratization within the firm. It discusses workers' cooperatives, collective capital ownership and industrial democracy. The book proposes new institutions and policies by which a self-managed sector could be promoted under capitalism.